Existing RC structures strengthened by ties under seismic sequences considering uncertainty. Issue 2 (22nd April 2019) - Liolios, Angelos; Hatzigeorgiou, George; Liolios, Konstantinos; Spyridis, Panagiotis
Abstract: The probabilistic seismic analysis of existing reinforced concrete (RC) structures, which are strengthened by cable elements (tension‐ties), is numerically investigated. Emphasis is given to uncertainties for the estimation of structural input parameters, common to old RC structures, and to accumulative effects of seismic sequences on the structure response. Monte Carlo techniques are used and the unilateral behavior of the cable elements, which can undertake tension stresses only, is strictly taken into account.